English Teachers' Challenges and Strategies in Teaching English for Special Needs Students - Beta, Ria; Upa, Yunika (ITScience (Information Technology and Science), 2025)
The implementation of inclusive education policies in Indonesia mandates that all students, including those with special needs, receive quality English language instruction. However, English teachers in rural special education settings face unique pedagogical challenges that require specialized approaches and adaptive instruction. Limited research exists on the specific challenges and instructional strategies employed by English teachers working with special needs students in resource-constrained rural environments. This study aims to examine the challenges encountered by English teachers and analyze the teaching strategies implemented when instructing English to special needs students in rural educational contexts. A qualitative narrative inquiry design was employed at public special needs school in Landak Regency, involving two English teachers with different educational backgrounds. Data collection utilized classroom observations, semi-structured interviews, and document analysis, focusing on teachers instructing students with hearing impairments and intellectual disabilities across combined junior and senior high school levels. The findings revealed three primary challenges: resource limitations, professional development gaps, and student-specific learning barriers. Both teachers successfully implemented four adaptive teaching strategies: explicit instruction, multi-sensory teaching approaches, metacognitive methods, and eclectic pedagogical frameworks. Despite resource constraints, teachers demonstrated remarkable creativity in developing context-appropriate teaching materials and implementing differentiated instruction tailored to specific disability categories. Effective English language teaching for special needs students is achievable in rural settings through teacher adaptability and strategic pedagogical modifications. The study contributes empirical evidence that quality inclusive education does not solely depend on extensive resources but rather on innovative teaching approaches and context-specific strategy implementation.